Reduction of the stress concentration around an elliptic hole by using a functionally graded layer - Yang, Quanquan; Gao, Cun-Fa (Acta mechanica, 2016)
The aim of this paper is to study the problem of stress concentration in an infinite plate with an elliptic hole reinforced by a functionally graded layer based on the complex variable method combined with the technique of conformal mapping. With using the method of piece-wise homogeneous layers, the general solution for the functionally graded layer having normal arbitrary elastic properties is derived when the plate is subjected to arbitrary constant loads at infinity, and then numerical results are presented for several special examples. It is found that the existence of the functionally graded layer can influence the stress distribution in the plate, and thus choosing proper variations of the normal elastic properties and proper thicknesses of the layer can effectively reduce the stress concentration around the elliptic hole.